Maritime Dispute Resolution With Mediation Techniques - Gayo, Sabela (SASI, 2023)
Introduction: In resolving ordinary maritime disputes related to national borders, from several types of dispute resolution, mediation is the right way to resolve disputes involving third parties.Purposes of the Research: This paper aims to find out that in resolving martim aurann disputes the law is contained in international law, namely UNCLOS 1982 which regulates martim disputes.Methods of the Research: The type of research is normative juridical with analysis using legal documents in the form of primary legal materials, secondary legal materials, and tertiary legal materials.Results of the Research: Alternative settlement of territorial boundary disputes can be done by, first, referring to UNCLOS 1982 through Bilateral Mutual Agreement in drawing a temporary line (equidistant line) using the equity principle and considering relevant factors and the possibility of modifying the equidistant line with the diplomatic approach of both countries, second, through the ASEAN mechanism, and. third, through the mechanism of the International Court of justice by promoting equitable principles and relevant circumstances.However, resolving with the second alternative is more appropriate because it can use mediation methods in maritime dispute resolution.